(untitled) (Homoeopathy for All, 2024)
Anosmia, defined as the loss of the sense of smell, can significantly impair an individual’s quality of life; however, its importance is frequently underestimated. The sense of smell is crucial for both the appreciation of daily experiences, such as food and nature, and for the identification of potential dangers, including gas leaks and spoiled food. The failure to detect these odors may jeopardize safety and well-being. Anosmia can arise from multiple etiologies, such as viral infections, nasal obstructions, or neurodegenerative disorders, including Alzheimer’s and Parkinson’s diseases. The prevalence of smell loss is significant among older populations, with approximately 3.2% of U.S. adults over 40 affected, a statistic that increases to 14–22% in individuals over 60. Anosmia is frequently unrecognized, primarily due to the absence of formal olfactory testing in routine health examinations, resulting in patients relying on self-reporting of their symptoms.